2021
DOI: 10.15415/jtmge.2021.121002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Performance on Financial Performance: Empirical Evidence from Indian Banking Sector

Abstract: There has been long-standing debate over whether or not firms gain economic competiveness from reducing their impact on the environment. Although ample literature is available on association between environmental performance and financial performance across various sectors, little empirical evidence is available in context of Indian banking sector. This research aims to analyze whether there is any significant relationship between environmental performance and financial performance of banks operating in India … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Furthermore, in the study by Chang [8], it was found that the environmental performance of companies in China from 2008-2012 significantly influenced the company's financial performance, which was proxied to Return on Assets. However, there are different research results found by Munjal & Malarvizhi [9], where it was found that in banking companies in India, the environmental performance achieved by the company did not significantly affect the company's financial Performance.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, in the study by Chang [8], it was found that the environmental performance of companies in China from 2008-2012 significantly influenced the company's financial performance, which was proxied to Return on Assets. However, there are different research results found by Munjal & Malarvizhi [9], where it was found that in banking companies in India, the environmental performance achieved by the company did not significantly affect the company's financial Performance.…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies that discussed EP's effect on FP found a positive influence [15,16]. Meanwhile, different studies have found that EP does not affect FP due to companies that are too focused on increasing profit orientation without paying attention to EP, which might be able to increase profits or improve the company's FP [9]. Based on the explanation above, EP and FP, the alternative hypotheses in this study are: H1: EP Affects FP…”
Section: Environmental Performance On Financial Performancementioning
confidence: 86%
“…The result reported was found to be consistent with prior studies by Adem (2022) reported a positive effect. Others include the studies of Munjal and Malarvizhi (2021); Uniamikogbo et al (2021) which reported positive effects. In addition the studies of Onyeiwu and Sulangna (2021); Hafsa (2020); Getzner and Moroz (2020); Olaore et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, other prior studies have reported contradictory results. Gentile-Ludecke et al (2019) reported that internationalization had a negative effect on financial stability, similarly, Hernández-Perlines et al (2020) reported that there was an inverse relationship between internationalization and financial stability, suggestively, some banks go into crossborder internationalization of banking operations for egoistical and corporate image purposes not specifically for the stabilization of their financial status (Mendoza et al, 2020;Munjal & Malarvizhi, 2021). Consequent to inconclusiveness and conflicting opinions and results, existing gaps in literature become more obvious.…”
Section: Introductionmentioning
confidence: 99%
“…This study adopted 15 major environmental indicators to evaluate the environmental information disclosed in the bank reports. As seen in Table 1, this set of indicators is adopted and modified from previous studies (Allet, 2011;Fijałkowska et al, 2018;Kaium Masud et al, 2017;Munjal and Malarvizhi, 2021;Nor et al, 2016;Solovida and Latan, 2017). The chosen indicators comprehensively represent all the major environmental initiatives and practices of banking institutions.…”
Section: Independent Variablementioning
confidence: 99%